Scleral lens sensor for ocular electrolyte analysis - Yetisen,AK; Jiang,N; Castaneda,Gonzalez CM; Erenoglu,ZI; Dong,J; Dong,X; Stößer,S; Brischwein,M; Butt,H; Cordeiro,MF; Jakobi,M; Hayden,O; et al. (Advanced Materials, 2020)
The quantitative analysis of tear analytes in point-of-care settings can enable early diagnosis of ocular diseases. Here, a fluorescent scleral lens sensor is developed to quantitatively measure physiological levels of pH, Na+ , K+ , Ca2+ , Mg2+ , and Zn2+ ions. Benzenedicarboxylic acid, a pH probe, displays a sensitivity of 0.12 pH units within pH 7.0-8.0. Crown ether derivatives exhibit selectivity to Na+ and K+ ions within detection ranges of 0-100 and 0-50 mmol L-1 , and selectivities of 15.6 and 8.1 mmol L-1 , respectively. A 1,2 bis(o-aminophenoxy)ethane-N,N,-N',N'-tetraacetic-acid-based probe allows Ca2+ ion sensing with 0.02-0.05 mmol L-1 sensitivity within 0.50-1.25 mmol L-1 detection range. 5-Oxazolecarboxylic acid senses Mg2+ ions, exhibiting a sensitivity of 0.10-0.44 mmol L-1 within the range of 0.5-0.8 mmol L-1 . The N-(2-methoxyphenyl)iminodiacetate Zn2+ ion sensor has a sensitivity of 1 µmol L-1 within the range of 10-20 µmol L-1 . The fluorescent sensors are subsequently multiplexed in the concavities of an engraved scleral lens. A handheld ophthalmic readout device comprising light-emitting diodes (LEDs) and bandpass filters is fabricated to excite as well as read the scleral sensor. A smartphone camera application and an user interface are developed to deliver quantitative measurements with data deconvolution. The ophthalmic system enables the assessment of dry eye severity stages and the differentiation of its subtypes.